Alleviating Poverty Of Indigenous Papuans (OAP) Through Community Empowerment By The Jayawijaya Regency Social Service Papua Mountain Province - Yanti Liliana Pratiwi Sunarya Kobogau; Halilul Khairi; Eko Budi Santoso (Jurnal Scientia, 2024)
Community empowerment is a crucial approach in efforts to eradicate poverty among Indigenous Papuans in Jayawijaya Regency. Jayawijaya Regency, Papua Mountain Province, as a region rich in natural resources, often faces complex challenges in terms of development and welfare of its people. This research explores various empowerment programs that can have a positive impact in overcoming poverty among indigenous Papuans. This research uses a qualitative approach by conducting in-depth interviews and observations. The researcher also applies pure research and analyzes using NVIVO on empowerment programs that have been implemented in several indigenous Papuan community. The research results show that an empowerment approach that is oriented towards Education/Training (skills development), Economics, Social Culture and Policies and Regulations to strengthen local capacity has a significant impact in improving welfare and reducing poverty levels. Successful empowerment programs focus on development local potential, including sustainable use of natural resources, increasing access to education and health. In addition, the integration of culture and local wisdom in programs is key in ensuring sustainability and acceptance by local communities. Where geographic and socio-economic factors often become obstacles to development, collaboration between government, non-governmental organizations, the private sector and local communities is essential in ensuring the success of empowerment programs. This research concludes that through a holistic and sustainable community empowerment approach, significant poverty alleviation can be achieved among Indigenous Papuans, while strengthening their cultural sovereignty and dignity.